2021
DOI: 10.48550/arxiv.2112.03287
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AdS$_3$ holography for non-BPS geometries

Bogdan Ganchev,
Stefano Giusto,
Anthony Houppe
et al.

Abstract: By using the approach introduced in [1] we construct non-BPS solutions of 6D (1, 0) supergravity coupled to two tensor multiplets as a perturbation of AdS 3 ×S 3 . These solutions are both regular and asymptotically AdS 3 × S 3 , so according to the standard holographic framework they must have a dual CFT interpretation as non-supersymmetric heavy operators of the D1-D5 CFT. We provide quantitative evidence that such heavy CFT operators are bound states of a large number of light BPS operators that are mutuall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…One can then try to use these "low-temperature states" as a basis for more general classes of black holes. More recent calculations, like those in [23,24], also suggest that highly coherent black-hole microstates at finite temperature can be constructed by putting the system in a "box" created by anti-de-Sitter (AdS) boundary conditions. Such coherent states then represent black holes in equilibrium with the radiation they produce.…”
Section: Fuzzballs and Microstate Geometriesmentioning
confidence: 97%
“…One can then try to use these "low-temperature states" as a basis for more general classes of black holes. More recent calculations, like those in [23,24], also suggest that highly coherent black-hole microstates at finite temperature can be constructed by putting the system in a "box" created by anti-de-Sitter (AdS) boundary conditions. Such coherent states then represent black holes in equilibrium with the radiation they produce.…”
Section: Fuzzballs and Microstate Geometriesmentioning
confidence: 97%
“…However, a series of breakthroughs [43,28,29,[44][45][46][47][48][49] not only made the solution of this problem possible, but enabled the systematic construction of vast families of such microstate geometries [50,51,31,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67]. Dissecting the "no-go" theorems revealed that the mechanism underlying microstate geometries is the only way to create non-trivial, horizonless, time-independent solitonic solutions with black-hole mass and charges [68,69].…”
Section: "Macroscopic" Microstate Geometriesmentioning
confidence: 99%
“…Over the years, there has been some construction of non-supersymmetric microstate geometries, but these have often led to extremal solutions, or solutions with very high angular momenta [137, 151-153, 73, 154-160]. However, the last year has seen some spectacular progress in the systematic construction of very interesting, more physical classes of non-supersymmetric microstate geometries [66,67,[161][162][163]. These constructions are quite new, but they underline how some of the remarkable features of supersymmetric microstate geometries are shared by non-supersymmetric counterparts.…”
Section: Non-bps Microstate Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed holographic description of superstrata has passed precision tests [16][17][18]. The most recently constructed solutions in this programme include both supersymmetric and non-supersymmetric solutions [19][20][21].…”
mentioning
confidence: 99%